2021
DOI: 10.3390/s21082586
|View full text |Cite
|
Sign up to set email alerts
|

Role of AI and Histopathological Images in Detecting Prostate Cancer: A Survey

Abstract: Prostate cancer is one of the most identified cancers and second most prevalent among cancer-related deaths of men worldwide. Early diagnosis and treatment are substantial to stop or handle the increase and spread of cancer cells in the body. Histopathological image diagnosis is a gold standard for detecting prostate cancer as it has different visual characteristics but interpreting those type of images needs a high level of expertise and takes too much time. One of the ways to accelerate such an analysis is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 106 publications
2
18
0
Order By: Relevance
“…Recently, automated artificial intelligence algorithms can be utilized to distinguish abnormal characteristics based on a specific symptom. In agreement with other related studies [30,31,32], artificial intelligence has shown dramatic growth in environmental monitoring and medical health applications, mainly in enhancing histopathology imagery, which can provide a breeding ground for developing bioinformatics applications in various fields.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, automated artificial intelligence algorithms can be utilized to distinguish abnormal characteristics based on a specific symptom. In agreement with other related studies [30,31,32], artificial intelligence has shown dramatic growth in environmental monitoring and medical health applications, mainly in enhancing histopathology imagery, which can provide a breeding ground for developing bioinformatics applications in various fields.…”
Section: Discussionsupporting
confidence: 87%
“…Observation of biodegradable implants requires an accurate localization of the implant and its borders, especially because of the constant changes over time. There lies the challenge of unclear border areas and artefacts, where individual judgement of the operator doing the analysis can affect the resulting data [ 89 ]. The use of machine learning, such as deep neural networks [ 90 , 91 ], has a potential to improve the speed and accuracy of image analysis, reducing the effect of human error and differences in individual judgements.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of CNN models, most of the histopathological image classification models [24], [25] are originated from the popular classification backbones from the natural image classification. However, histopathological image classification faces different challenges, such as extremely large image resolution, deficiency of labels and multiscale information integration [26]. WSI-Net [27] model was proposed to add an additional classification branch to discard the normal tissue in order to save computational resources.…”
Section: A Histopathological Image Classificationmentioning
confidence: 99%